How I survived bullies, broccoli, and Snake Hill - Patterson, James, 1947- (Patterson, James, 1947- Middle school novels., 2013)
"When Rafe Khatchadorian is sent to Camp Wannamorra, he teams up with his bunk mates to fend off the more "popular" kids' plans to ruin their summer"--